2016
DOI: 10.3847/0004-637x/826/2/192
|View full text |Cite
|
Sign up to set email alerts
|

Constraint on a Cosmological Variation in the Proton-to-Electron Mass Ratio From Electronic Co Absorption

Abstract: -Carbon monoxide (CO) absorption in the sub-damped Lyman-α absorber at redshift z abs ≃ 2.69, toward the background quasar SDSS J123714.60+064759.5 (J1237+0647), was investigated for the first time in order to search for a possible variation of the proton-to-electron mass ratio, µ, over a cosmological time-scale.The observations were performed with the Very Large Telescope/Ultraviolet and Visual Echelle Spectrograph with a signal-to-noise ratio of 40 per 2.5 km s −1 per pixel at ∼ 5000Å. Thirteen CO vibrationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 78 publications
(141 reference statements)
6
34
0
Order By: Relevance
“…Evans et al 2014), solar twin stars (e.g. Daprà et al 2015Daprà et al , 2016 or spectra of the same object on better-calibrated spectrographs (e.g. Kotuš et al 2017).…”
Section: Wavelength Scale Shifts and Distortionsmentioning
confidence: 99%
“…Evans et al 2014), solar twin stars (e.g. Daprà et al 2015Daprà et al , 2016 or spectra of the same object on better-calibrated spectrographs (e.g. Kotuš et al 2017).…”
Section: Wavelength Scale Shifts and Distortionsmentioning
confidence: 99%
“…Salumbides et al (2012) reported high-accuracy laboratory wavelength measurements, with an accuracy of ∆λ/λ = 3 × 10 −7 , for this band system, allowing to extract a constraint on a varying µ at a level of ∼ 10 −5 . Daprà et al (2016) reported the first measurement of ∆µ/µ = (0.7 ± 1.6 stat ± 0.5 syst ) × 10 −5 from electronic CO absorption only in the system SDSS J123714.60+064759.5, which was then combined with the ∆µ/µ value derived from H 2 absorption. Noterdaeme et al (2017) presented a detailed study of the absorption system towards J0000+0048, including CO, H 2 , deuterated molecular hydrogen, HD, as well as atomic species and dust, in order to understand the chemical and physical properties of the absorbing gas.…”
Section: Introductionmentioning
confidence: 99%
“…The J = 4 lines are at the noise level for most bands, but included in the fit. We used the updated molecular data summarised in Daprà et al (2016). Accurate wavelengths were obtained through calibration by laser and VUV synchrotron studies (Salumbides et al 2012;Niu et al 2013Niu et al , 2015, while oscillator strengths and damping constants were carefully re-evaluated taking into account an updated perturbation analysis.…”
Section: Carbon Monoxidementioning
confidence: 99%